Berteroa physocarpa (Brassicaceae), a new species from NW Turkey based on morphological and molecular data - Yüzbaşioğlu, Sirri; Al-Shehbaz, Ihsan A.; Yüzbaşioğlu Eli̇f; Dalyan, Eda (Phytotaxa, 2017)
Berteroa physocarpa, a new species from the subalpine-alpine zone (1600−2200 m) of northwest Anatolia, is described and illustrated. It shares with the other species of Berteroa 2n=16 and morphologically is readily distinguished from them by having distinctly inflated fruit with glabrous valves. Sequences of nuclear ribosomal transcribed spacer (ITS) region were used to determine the relationship of Berteroa species using maximum likelihood methods. The phylogenetic results confirmed the recently established systematic history of Berteroa and also supported the recognition of this new species.